To the problem about thermal deformation of chill auxiliaries - M. A. Sadoha; B. A. Krajev; A. S. Mironov; N. E. Bondarik; V. I. Gutko (Литьë и металлургия)
There is shown the mechanism and described the kinetics of thermal deformations of chill auxiliaries. There are carried out the concrete experiments and presented their results. There are described the basic existing methods of chill auxiliaries thermal deformations control and shown their defaults.